Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1152/ajprenal.00326.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain modulation of endothelial calcium signaling in descending vasa recta

Abstract: Using fura 2-loaded vessels, we tested whether ouabain modulates endothelial cytoplasmic calcium concentration ([Ca(2+)](CYT)) in rat descending vasa recta (DVR). Over a broad range between 10(-10) and 10(-4) M, ouabain elicited biphasic peak and plateau [Ca(2+)](CYT) elevations. Blockade of voltage-gated Ca(2+) entry with nifedipine did not affect the response to ouabain mitigating against a role for myo-endothelial gap junctions. Reduction of extracellular Na(+) concentration ([Na(+)](o)) or Na(+)/Ca(2+) exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 54 publications
3
25
1
Order By: Relevance
“…2-APB is frequently used to inhibit IP 3 receptors but is known to have other effects, particularly to block store-operated cation channels. We previously showed that 2-APB suppresses DVR endothelial [Ca 2ϩ ] CYT responses to ouabain (38). In this study, however, it did not affect STIC oscillations.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…2-APB is frequently used to inhibit IP 3 receptors but is known to have other effects, particularly to block store-operated cation channels. We previously showed that 2-APB suppresses DVR endothelial [Ca 2ϩ ] CYT responses to ouabain (38). In this study, however, it did not affect STIC oscillations.…”
Section: Discussioncontrasting
confidence: 64%
“…That inhibition has been hypothesized to elevate subplasmalemmal Na ϩ and Ca 2ϩ concentrations through reduction of NCX activity, resulting in an increase in Ca 2ϩ content of ER/SR stores and bulk cytoplasm (4). Functional studies showed that this favors an increase in microvessel contractility and a rise in the Ca 2ϩ released by agonists (3,38,45). Given the dependence of STICs on Ca 2ϩ store release, we tested whether ouabain would affect their occurrence in DVR pericytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence favoring that hypothesis has been accumulating. Low-dose (10 -100 nM) ouabain enhances Ca 2ϩ release in smooth muscle and endothelium (2, 35) and increases resting cytoplasmic Ca 2ϩ ([Ca 2ϩ ] CYT ) and myogenic tone (35,48).A role for OLF in hypertension is also well supported. Chronic administration of ouabain into rodents induces hypertension (26, 28), and many patients with essential hypertension have high plasma ouabain levels (43).…”
mentioning
confidence: 99%
“…Evidence favoring that hypothesis has been accumulating. Low-dose (10 -100 nM) ouabain enhances Ca 2ϩ release in smooth muscle and endothelium (2, 35) and increases resting cytoplasmic Ca 2ϩ ([Ca 2ϩ ] CYT ) and myogenic tone (35,48).…”
mentioning
confidence: 99%